A new linoleiyl arabinopyranoside from the bark of Bauhinia racemosa Lam and a new flavonoidal glycoside from the leaves of Cordia dichotoma Linn. Issue 20 (17th October 2016) - Rahman, Md. Azizur; Akhtar, Juber
Abstract: Phytochemical investigation is very valuable for the ethnomedicinally important plants Bauhinia racemosa Lam (BR) and Cordia dichotoma Linn (CD) used for the cure of variety of ailments. This study was thus designed for phytochemical investigation of BR bark and CD leaves. Phytoconstituents were isolated from the methanolic extracts of the plants by column chromatography using silica gel as stationary phase. The structures had been established on the basis of their physicochemical and spectral data, i.e. IR, 1 H NMR, 13 C NMR and MS. Elution of the columns with different solvents furnished six compounds (1 –6 ) from the methanolic extract of BR bark and three compounds (7 –9 ) from the methanolic extract of CD leaves which were structurally elucidated. The present phytochemical investigation reported several new compounds useful in increasing the existing knowledge of phytoconstituents from BR bark and CD leaves which is very valuable, as these drugs are used in the Indian traditional systems of medicine. Abstract :